Virtual exhibition as a tool for the treatment of obsessive compulsive disorder - Cardenas L., Gergina (2012)
In Mexico City 2.6% of population have Obsessive Compulsive Disorder, this is a that impact the quality of life in the persons who presents, it was classified by WHO like tenth disability cause in the world, it´s for this reason that needs closer attention about mental health professionals, there are several studies about treatment for this disorder, between these we can find the exposure and response prevention treatment and cognitive treatment. The treatment could be perceived like aversive, and between 25 and 35 per cent of patients drop out the treatment to be due to experimented anxiety during exposure, Virtual Teaching Laboratory presents avirtual reality based treatment for expose obsessive compulsive patients in a controlled way and lower aversive, this treatment it’s based in exposure and response prevention , but give an advantage fortherapist, who can graduate in a better way the stimulus and have the possibility of reply the events the time it was necessary. Virtual environments developed for this purpose are places that are in context with Mexican culture and are related with dailylife for helps patient to improve his quality of life and reduce avoidance and anxiety scores.